Climate Sensitive Urban Design pada Kawasan Pecinan Kota Semarang - Rina Kurniati; Wakhidah Kurniawati; Diah Intan Kusumo Dewi; Talitha Zuleika Islamey (TATALOKA, 2020)
The Chinatown area is a historic area that has a high building density and has a grid-shaped pattern due to its function as trade and services. The various designations of the area function so that the high activity is carried out outside the room, especially on weekends. This study aims to provide direction for environmental management in the Chinatown area of Semarang City as an effort to mitigate climate change disasters with the concept of Climate Sensitive Urban Design. Data obtained by field observations then identified the Building Coverage Ratio (BCR) and floor area Ratio (FAR). Measurement of air temperature, wind speed and humidity is carried out in the morning, afternoon and evening. Simulated data using ArcGis 10.3 to test the thermal comfort. Based on that, the Chinatown is classified as Uncomfortable area more than 27 ° C. The microclimate of the Chinatown area is influenced by landuse, building, and the frequency of traffic. So the concept of the climate sensitive urban design is suitable for the Chinatown area with optimization of the potted plants, hanging plants on the canopy, vine vegetation on walls and use public transportation modes to the area.